Hadith #2154 - Sunan Abi Dawud - Abu 'Alqama أبو علقمة; Abu Sa'id al-Khudri; Qatada قتادة; Sa'id bin Abi Sa'id; Salah bin Abi Maryam صالح بن أبي مريم الضبعي - أبو الخليل; Ubaidullah bin 'Umar al-Qawariri عبيد الله بن عمر القواريري; Yazid bin Zari' يزيد بن زريع (Sunan Abi Dawud)
The aforesaid tradition has also been transmitted by Abu Hurairah through a different chain of narrators. This version adds “The fornication of ear is hearing.”
Grade: Sahih

Hadith #2156 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Amr bin 'Awn/'Auf bin Aws; Jabir Bun Nauf, Abu al-Wadak جبر بن نوف أبو الوداك; Qays bin Wahb al-Hmdany قيس بن وهب الهمداني الكوفي; Sharayk bin 'Abdullah شريك بن عبد الله النخعي (Sunan Abi Dawud)
Abu Al Darda said “The Apostle of Allaah(ﷺ) was in a battle. He saw a woman who was nearing the time when she was to deliver a child. “He said “Perhaps the master has intercourse with her.”. They(the people) said “Yes”. He said “I am inclined to invoke a curse on him which will enter his grave with him. How can he make it (the child) an heir when it is not lawful for him? How can he take it into his service when that is not lawful for him?”
Grade: Sahih

Hadith #2169 - Sunan Abi Dawud - Abdullah bin Abi Najih عبد الله بن أبي نجيح; Abu Sa'id al-Khudri; Mujahid bin Jabir مجاهد بن جبر; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
If a man has sexual intercourse (with menstruating woman) during her bleeding, he should give one dinar as sadaqah, and if he does so when bleeding has stopped, he should give half a dinar as sadaqah.
Grade: Da'if

Hadith #2170 - Sunan Abi Dawud - Aban bin Tghlb أبان بن تغلب; Abu Sa'id al-Khudri; Muhammad bin 'AR bin Thauban محمد بن عبد الرحمن بن ثوبان; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
Abu Sa’id reported “The people mentioned about withdrawing the penis before the Prophet (ﷺ). He said “Why one of you does so? He did not say “One of you should not do so”. Every soul that is to be born, Allaah will create it. Abu Dawud said “Qaza’ah is a client of Ziyad”
Grade: Sahih

Hadith #2360 - Sunan Abi Dawud - Abdullah bin Khabab عبد الله بن خباب الأنصاري النجاري; Abu Sa'id al-Khudri; Bakr bin Madr bin Muhammad بكر بن مضر بن محمد; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Yazid bin 'Abdullah bin Usama B. al-Haad يزيد بن عبد الله بن أسامة بن الهاد (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) prohibited perpetual fasting. They (the people) said: You keep perpetual fasting, Messenger of Allah. He said: My position is not like that you yours. I am provided with food and drink.
Grade: Sahih

Hadith #2416 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Amr bin Yahya bin 'Ammara عمرو بن يحيى بن عمارة; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Wahayb bin Khalid bin 'Ajlan al-Bahli وهيب بن خالد بن عجلان الباهلي; Yahya bin 'Ammara يحيى بن عمارة بن أبي حسن الأنصاري (Sunan Abi Dawud)
I attended the ‘Id (prayer) along with ‘Umar. He offered prayer before the sermon. He then said: The Messenger of Allah (ﷺ) prohibited fasting on these two days. As regards Id al-Adha, you eat the meat of your sacrificial animals. As for ‘Id al-Fitr, you break (i.e. end) your fast.
Grade: Sahih

Hadith #2458 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Jarir bin 'Abdul Hameed al-Razi جرير بن عبد الحميد أبو عبد الله الضبي; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Uthman bin Muhammad (Sunan Abi Dawud)
It is not allowable for a woman to keep (voluntary) fast when her husband is present without his permission, and she may not allow anyone to enter his house without his permission.
Grade: Sahih

Hadith #2476 - Sunan Abi Dawud - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abu Sa'id al-Khudri; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ata'a bin Yazid al-Laithi al-Junda'i عطاء بن يزيد الليثي الجندعي; Mu'ml bin al-Fadl مؤمل بن الفضل (Sunan Abi Dawud)
A’ishah(may Allaah be pleased with her) said “One of the wives of the Apostle of Allaah(ﷺ) observed I’tikaf along with him (in the mosque). She would see yellowness and redness. Sometimes we would place a washbasin while she prayed.”
Grade: Sahih

Hadith #2484 - Sunan Abi Dawud - Abu Sa'id al-Khudri; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ata'a bin Yazid al-Laithi al-Junda'i عطاء بن يزيد الليثي الجندعي; Hisham bin 'Abdul Malik al-Tayalasi هشام بن عبد الملك أبو الوليد الطيالسي; Sulaiman bin Khatir al-'Abdi سليمان بن كثير العبدي (Sunan Abi Dawud)
The Prophet (ﷺ) said: A section of my community will continue to fight for the right and overcome their opponents till the last of them fights with the Antichrist.
Grade: Sahih

Hadith #2509 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Sa'id al-Khudri; Amr bin al-Harith bin Ya'qub عمرو بن الحارث; Sa'id bin Mnswr bin Sh'bh سعيد بن منصور بن شعبة; Yazid bin Abi Habib يزيد بن أبي حبيب (Sunan Abi Dawud)
Zaid bin Khalid al Juhani reported that Apostle of Allaah(ﷺ) as saying “He who equips a fighter in Allaah’s path has taken part in the fighting. And he looks after a fighter’s family when he is away has taken part in the fighting.”
Grade: Sahih

Hadith #2529 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Sa'id al-Khudri; Amr bin al-Harith bin Ya'qub عمرو بن الحارث; Sa'id bin Mnswr bin Sh'bh سعيد بن منصور بن شعبة (Sunan Abi Dawud)
The name of the narrator Abu al-‘Abbas, a poet, is al-Sa’ib b. Farrukh.
Grade: Sahih

Hadith #2607 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ali bin Bhr bin Bry علي بن بحر بن بري; Hatm bin Isma'il al-Madni حاتم بن إسماعيل المدني; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Nafie' نافع مولى ابن عمر (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: A single rider is a devil, and a pair of riders are a pair of devils, but three are a company of riders.
Grade: Hasan

Hadith #2647 - Sunan Abi Dawud - Abu Sa'id al-Khudri; al-Mandhar bin Malik bin Qata' المنذر بن مالك بن قطعة - أبو نضرة العبدي (Sunan Abi Dawud)
Ibn Umar was sent with a detachment of the Messenger of Allah (ﷺ). The people wheeled round in flight. He said: I was one of those who wheeled round in flight. When we stopped, we said (i.e. thought): How should we do? We have run away from the battlefield and deserve Allah’s wrath. Then we said (thought): Let us enter Medina, stay there, and go there while no one sees us. So we entered (Medina) and thought: If we present ourselves before the Messenger of Allah (ﷺ), and if there is a chang
Grade: Da'if

Hadith #2782 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Ja'far bin Msafr bin Rashid جعفر بن مسافر بن راشد; Muhammad bin 'AR bin Thauban محمد بن عبد الرحمن بن ثوبان; Muhammad bin Abi Fadayk محمد بن إسماعيل بن مسلم بن أبي فديك (Sunan Abi Dawud)
When the Messenger of Allah (ﷺ) arrived from his hajj, he entered Medina, and made (his camel) kneel down at the gate of his mosque; and he entered it and offered two rak’ahs of prayer; he then returned to his home. Nafi’ said: Ibn Umar also used to do so.
Grade: Hasan Sahih

Hadith #2795 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Hafs bin Ghyath حفص بن غياث; Ja'far bin Rabi'ya bin Shrhbyl جعفر بن ربيعة بن شرحبيل; Yahya bin Ma'in يحيى بن معين (Sunan Abi Dawud)
The Prophet (ﷺ) sacrificed two horned rams which were white with black markings and had been castrated. When he made them face the qiblah, he said: I have turned my face towards Him. Who created the heavens and the earth, following Abraham’s religion, the true in faith, and I am not one of the polytheists. My prayer, and my service of sacrifice, my life and my death are all for Allah, the Lord of the Universe, Who has no partner. That is what I was commanded to do, and I am one of the Muslim
Grade: Da'if

Hadith #2826 - Sunan Abi Dawud - Abdullah bin Mubarak عبد الله بن المبارك; Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Sa'id al-Khudri; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Jabir Bun Nauf, Abu al-Wadak جبر بن نوف أبو الوداك; Masdad bin Masrhad مسدد بن مسرهد بن مسربل (Sunan Abi Dawud)
Ibn Isa added: (Ibn Abbas) and AbuHurayrah said: The Messenger of Allah (ﷺ) forbade the devil’s sacrifice. AbuIsa added in his version: This refers to the slaughtered animal whose skin cut off, and is then left to die without its jugular veins being severed.
Grade: Da'if

Hadith #2865 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Ahmed bin Salah al-Masri أحمد بن صالح المصري; Muhammad bin 'Abdur Rahman b. Abi Dh'ab محمد بن عبد الرحمن بن أبي ذئب; Muhammad bin Abi Fadayk محمد بن إسماعيل بن مسلم بن أبي فديك (Sunan Abi Dawud)
A man asked the Messenger of Allah (ﷺ): Messenger of Allah, which sadaqah (charity) is the best ? He replied: (The best sadaqah is) that you give something as sadaqah (charity) when you are healthy, greedy, expect survival and fear poverty, and not that you postpone it until your death. and then you say: For so-and-so is such-and-such, and for so-and-so is such-and-such, while it was already for so-and-so.
Grade: Sahih

Hadith #3113 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Muhammad bin Ibrahim bin al-Harith محمد بن إبراهيم بن الحارث; Sa'id bin Abi Maryam سعيد بن أبي مريم; Yahya bin Ayoub al-Ghafiqi يحيى بن أيوب الغافقي; Yazid bin 'Abdullah bin Usama B. al-Haad يزيد بن عبد الله بن أسامة بن الهاد (Sunan Abi Dawud)
I heard the Messenger of Allah (ﷺ) say three days before his death: No one of you dies but he had good faith in Allah.
Grade: Sahih

Hadith #3116 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Amarah bin Ghazya bin al-Harith عمارة بن غزية بن الحارث; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Yahya bin 'Ammara يحيى بن عمارة بن أبي حسن الأنصاري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: If anyone’s last words are “There is no god but Allah” he will enter Paradise.
Grade: Sahih

Hadith #3127 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Ibrahim bin Musa al-Razi al-Fara' إبراهيم بن موسى الرازي الفراء; Muhammad bin al-Hasan bin Atyh محمد بن الحسن بن عطية; Muhammad bin Rabi'ya al-Klaby محمد بن ربيعة الكلابي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) prohibited us to wail.
Grade: Sahih

Hadith #3157 - Sunan Abi Dawud - Abu Sa'id al-Khudri; al-Mandhar bin Malik bin Qata' المنذر بن مالك بن قطعة - أبو نضرة العبدي; al-Mstmr bin al-Ryan المستمر بن الريان; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي (Sunan Abi Dawud)
I was one of those who washed Umm Kulthum, daughter of the Prophet (ﷺ), when she died. The Messenger of Allah (ﷺ) first gave us lower garment, then shirt, then head-wear, then cloak (which covers the whole body), and then she was shrouded in another garment. She said: The Messenger of Allah (ﷺ) was sitting at the door, and he had shroud with him. He gave us the garments one by one.
Grade: Da'if

Hadith #3263 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Ahmad bin Hanbal أحمد بن حنبل; Ikrama bin 'Ammar عكرمة بن عمار العجلي أبو عمار اليمامي; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
The oath which the Messenger of Allah (ﷺ) often used was this: No, by Him who overturns the hearts.
Grade: Sahih

Hadith #3292 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Ubaidullah bin Zhr عبيد الله بن زحر; Uqba bin 'Amir al-Juhayni; Yahya bin Sa'id al-Ansari يحيى بن سعيد الأنصاري; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: No vow must be taken to do an act of disobedience, and the atonement for it is the same as for an oath. Ahmad b. Muhammad al-Marwazi said: The correct chain of this tradition is: ‘Ali b. al-Mubarak, from Yahya b. Abi Kathir, from Muhammad b. al-Zubair, from his father, on the authority of ‘Imran b. Husain from the Prophet (ﷺ) Abu Dawud said: By this he (al-Marwazi) means that the narrator Sulaiman b. Arqam had some misunderstanding about this traditi
Grade: Sahih

Hadith #3376 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Ahmed bin 'Amr bin al-Sarh أحمد بن عمرو بن السرح أبو الطاهر; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ata'a bin Yazid al-Laithi al-Junda'i عطاء بن يزيد الليثي الجندعي; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Abi Dawud)
The Prophet (ﷺ) forbade the type of sale which involves risk (or uncertainty) and a transaction determined by throwing stones.
Grade: Sahih

Hadith #3377 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Sa'id al-Khudri; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ata'a bin Yazid al-Laithi al-Junda'i عطاء بن يزيد الليثي الجندعي; Ma'mar bin Rashid معمر بن راشد (Sunan Abi Dawud)
The Prophet (ﷺ) forbade two types of business transactions and two ways of dressing. The two types of business transactions are mulamasah and munabadhah. As regards the two ways of dressing, they are the wrapping of the samma’, and that when a man wraps himself up in a single garment while sitting in such a way that he does not cover his private parts or there is no garment on his private parts.
Grade: Sahih

Hadith #3378 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Ahmed bin Salah al-Masri أحمد بن صالح المصري; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Amir bin Sa'd ibn Abi Waqqas عامر بن سعد بن أبي وقاص; Anbs'h bin Khalid bin Yazid عنبسة بن خالد بن يزيد; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Abi Dawud)
“Wearing the samma’ means that a man puts his garment over his left shoulder and keeps his right side uncovered. Munabadhah means that a man says (to another): If I throw this garment to you, the sale will be certain. Mulamasah means that a man touches it (another’s garment) with his hand and neither he unfolds it nor turns it over. When he touched it, the sale becomes binding.
Grade: Sahih

Hadith #3417 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Ali bin Da'ud,Abu al-Mutawakkal al-Naji علي بن داود أبو المتوكل الناجي; Ja'far bin Iyas; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Wadah bin 'Abdullah al-Yashkari وضاح بن عبد الله اليشكري أبو عوانة (Sunan Abi Dawud)
I said: What do you think about it, Messenger of Allah? He said: A live coal between your shoulders which you have put around your neck or hanged it.
Grade: Sahih

Hadith #3418 - Sunan Abi Dawud - Abu Sa'id al-Khudri; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Hisham bin Hassan al-Azdi هشام بن حسان الأزدي القردوسي; Ibn Sirin محمد بن سيرين الأنصاري; Yazid bin Harun يزيد بن هارون (Sunan Abi Dawud)
Some of the Companions of Prophet (ﷺ) went on a journey. They encamped with a clan of the Arabs and sought hospitality from them, but they refused to provide them with any hospitality. The chief of the clan was stung by a scorpion or bitten by a snake. They gave him all sorts of treatment, but nothing gave him relied. One of them said: Would that you had gone to those people who encamped with you ; some of them might have something which could give you relief to your companion. (So they went a
Grade: Sahih

Hadith #3467 - Sunan Abi Dawud - Aabad bin al-Walid bin Khalid عباد بن الوليد بن خالد الغبري; Abu Sa'id al-Khudri; Atyh bin Sa'd bin Jnad'h عطية بن سعد بن جنادة; Muhammad bin 'Isa bin Hyan محمد بن عيسى بن حيان; Ziyad bin Khaythama al-Ja'fi زياد بن خيثمة الجعفي (Sunan Abi Dawud)
A man paid in advance for a palm-tree. It did not bear fruit that year. They brought their case for decision to the Prophet (ﷺ). He said: for which do you make his property lawful? He then said: Do not pay in advance for a palm-tree till they (the fruits) were clearly in good condition.
Grade: Da'if

Hadith #3468 - Sunan Abi Dawud - Abu Sa'id al-Khudri; al-Laith bin Sa'd الليث بن سعد; Ayyad bin 'Abdullah bin Sa'd عياض بن عبد الله بن سعد بن أبي سرح; Bukayr bin 'Abdullah bin al-Ashj بكير بن عبد الله بن الأشج; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone pays in advance he must not transfer it to someone else before he receives it.
Grade: Da'if

Hadith #3639 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abdullah bin 'Abdur Rahman bin Ma'mar عبد الله بن عبد الرحمن بن معمر; Abu Sa'id al-Khudri; Amr bin Yahya bin 'Ammara عمرو بن يحيى بن عمارة; Mhmwd bin Khalid محمود بن خالد; Muhammad bin 'Uthman al-Akhnasi محمد بن عثمان الأخنسي; Yahya bin 'Ammara يحيى بن عمارة بن أبي حسن الأنصاري (Sunan Abi Dawud)
‘Amr bin Shu’aib on his father’s authority said that his grandfather told that the Messenger of Allah (ﷺ) decided regarding the stream al-Mahzur that its water should be held back till it reached the ankles, and that the upper waters should then be allowed to flow to the lower.
Grade: Hasan Sahih

Hadith #3647 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Ali bin Da'ud,Abu al-Mutawakkal al-Naji علي بن داود أبو المتوكل الناجي; Musa bin Nafi', Abu Shahab al-Hanat موسى بن نافع الأسدي أبو شهاب الحناط (Sunan Abi Dawud)
Al-Muttalib ibn Abdullah ibn Hantab said: Zayd ibn Thabit entered upon Mu’awiyah and asked him about a tradition. He ordered a man to write it. Zayd said: The Messenger of Allah (ﷺ) ordered us not to write any of his traditions. So he erased it.
Grade: Da'if

Hadith #3665 - Sunan Abi Dawud - Abu Sa'id al-Khudri; al-'Ala' bin Bashyr al-Mzny العلاء بن بشير المزني; Bakr bin 'Amr Abu al-Siddique al-Naji بكر بن عمرو/ قيس; Ja'far bin Sulaiman al-Daba'i جعفر بن سليمان الضبعي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل (Sunan Abi Dawud)
I heard the Messenger of Allah (ﷺ) say: Only a ruler, or one put in charge, or one who is presumptuous, gives instructions.
Grade: Hasan Sahih

Hadith #3719 - Sunan Abi Dawud - Abu Sa'id al-Khudri; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ubaydullah bin 'Abdullah bin 'Utba عبيد الله بن عبد الله بن عتبة بن مسعود (Sunan Abi Dawud)
The apostle of allah (ﷺ) forbade drinking from the mouth of a water-skin, and riding the animal which feeds on filth and eating the animal which is killed in confinement. Abu Dawud said: Jallalah means an animal which eats filth and impurities.
Grade: Sahih

Hadith #3721 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Sa'id al-Khudri; Ahmed bin Salah al-Masri أحمد بن صالح المصري; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ubaydullah bin 'Abdullah bin 'Utba عبيد الله بن عبد الله بن عتبة بن مسعود (Sunan Abi Dawud)
Invert the head of the vessel and he drank from its mouth.
Grade: Da'if

Hadith #3822 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Sa'id al-Khudri; Ahmed bin Salah al-Masri أحمد بن صالح المصري; Amr bin al-Harith bin Ya'qub عمرو بن الحارث; Bakr bin Swad'h bin Thmamh بكر بن سوادة بن ثمامة (Sunan Abi Dawud)
He who eats garlic or onion must keep away from us. Or he said: must keep away from our mosque or must sit in his house. A dish containing green vegetables was brought to him, and noticing that it had an odour he asked (about it). He was told that it contained some vegetables. He then said: Bring it near, to one of his companion who was with him. When he saw it, he abominated eating it, and said: eat for I hold intimate converse with one with whom you do not. Ahmad b. Salih said: Ibn Wahb explai
Grade: Sahih

Hadith #3849 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Abu Sa'id al-Khudri; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
When the food cloth was removed, the Messenger of Allah (ﷺ) said: “praise be to Allah abundantly and sincerely, of such a nature as is productive of blessing, is not insufficient, Abandoned, or ignored, O our lord.”
Grade: Sahih

Hadith #3899 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Ali bin Da'ud,Abu al-Mutawakkal al-Naji علي بن داود أبو المتوكل الناجي; Ja'far bin Iyas; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Wadah bin 'Abdullah al-Yashkari وضاح بن عبد الله اليشكري أبو عوانة (Sunan Abi Dawud)
A man who was stung by a scorpion was brought to the Prophet (ﷺ). He said: Had he said the word: “I seek refuge in the perfect words of Allah from the evil of what He created, “he would not have been stung, or he said, “It would not have harmed him.”
Grade: Hasan

Hadith #3978 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Muhammad bin Yahya bin Abi Hazm محمد بن يحيى بن أبي حزم القطعي; Ubaid bin Aqyl عبيد بن عقيل (Sunan Abi Dawud)
Atiyyah ibn Sa’d al-Awfi said: I recited to Abdullah ibn Umar the verse: “It is Allah Who created you in a state of (helplessness) weakness (min da’f).” He said: (Read) min du’f. I recited it to the Messenger of Allah (ﷺ) as you recited it to me, and he gripped me as I gripped you.
Grade: Hasan

Hadith #3986 - Sunan Abi Dawud - Aban bin Tghlb أبان بن تغلب; Abu Sa'id al-Khudri; Atyh bin Sa'd bin Jnad'h عطية بن سعد بن جنادة (Sunan Abi Dawud)
Ubayy ibn Ka’b made me read the following verse as the Messenger of Allah (ﷺ) made him read: “in a spring of murky water” (fi ‘aynin hami’atin) with short vowel a after h.
Grade: Sahih

Hadith #3997 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Abu Sa'id al-Khudri; Atyh bin Sa'd bin Jnad'h عطية بن سعد بن جنادة; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Uthman bin Muhammad (Sunan Abi Dawud)
A man whom the Prophet (ﷺ) made the following verse read informed me, or he was informed by a man whom a man made the following verse read through a man whom the Prophet (ﷺ) made the following verse read: “For, that day His chastisement will be such as none (else) can be inflicted (la yu’adhdhabu) Abu Dawud said: ‘Asim, al-A’mash, Talhah b. Musarrif, Abu Ja’far Yazid b. al-Qa’qa’, Shaibah b. Nassah, Nafi’ b. ‘Abd al-Rahman, ‘Abd Allah b. Kathir al-Dari, Abu ‘Amr b. al-
Grade: Hasan

Hadith #3998 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Atyh bin Sa'd bin Jnad'h عطية بن سعد بن جنادة; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Zayd bin Akhzm زيد بن أخزم (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) related a tradition in which he mentioned the words “Jibril and Mikal” and he pronounced them “Jibra’ila wa Mika’ila.” Abu Dawud said: Khalaf said: I did not put the pen aside from writing letters (huruf) for forty years: nothing tired me (or made me incapable of writing), even Jibril and Mika’il did not tire me.
Grade: Da'if

Hadith #4005 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Sa'id al-Khudri; Ahmed bin Salah al-Masri أحمد بن صالح المصري; Ata ibn Yasar عطاء بن يسار أبو محمد مولى ميمونة; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Sulaiman bin Da'ud bin Da'ud سليمان بن داود بن داود بن علي; Zayd bin Aslam زيد بن أسلم (Sunan Abi Dawud)
‘Abd Allah (b. Mas’ud) was told that the people had read this verse: “She said: Now come, thou” (hita laka). He said: I read it as I have been taught ; it is dearer to me. It goes “wa qalat haita laka” (She said: Now come thou).
Grade: Sahih

Hadith #4017 - Sunan Abi Dawud - Abdur Rahman bin Abi Sa'id al-Khudri عبد الرحمن بن أبي سعيد; Abdur Rahman bin Ibrahim عبد الرحمن بن إبراهيم - دحيم; Abu Sa'id al-Khudri; al-Dahhak bin 'Uthman bin 'Abdullah الضحاك بن عثمان بن عبد الله بن خالد; Muhammad bin Abi Fadayk محمد بن إسماعيل بن مسلم بن أبي فديك; Zayd bin Aslam زيد بن أسلم (Sunan Abi Dawud)
I said: Messenger of Allah, from whom should we conceal our private parts and to whom can we show? He replied: conceal your private parts except from your wife and from whom your right hands possess (slave-girls). I then asked: Messenger of Allah, (what should we do), if the people are assembled together? He replied: If it is within your power that no one looks at it, then no one should look at it. I then asked: Messenger of Allah if one of us is alone, (what should he do)? He replied: Allah is
Grade: Hasan

Hadith #4019 - Sunan Abi Dawud - Abdullah bin Mubarak عبد الله بن المبارك; Abu Sa'id al-Khudri; al-Mandhar bin Malik bin Qata' المنذر بن مالك بن قطعة - أبو نضرة العبدي; Amr bin 'Awn/'Auf bin Aws; Sa'id bin Iyas al-Jariri سعيد بن إياس الجريري (Sunan Abi Dawud)
The Prophet (ﷺ) said: A man should not lie with another man and a woman should not lie with another woman without covering their private parts except a child or a father. He also mentioned a third thing which I forgot.
Grade: Da'if

Hadith #4092 - Sunan Abi Dawud - Abu Sa'id al-Khudri; al-Ala' bin 'Abdur Rahman bin Ya'qub العلاء بن عبد الرحمن; Hafs bin 'Umar bin al-Harith حفص بن عمر بن الحارث; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Abi Dawud)
A man who was beautiful came to the Prophet (ﷺ). He said: Messenger of Allah, I am a man who likes beauty, and I have been given some of it, as you see. And I do not like that anyone excels me (in respect of beauty). Perhaps he said: “even to the extent of thong of my sandal (shirak na’li)”, or he he said: “to the extent of strap of my sandal (shis’i na’li)”. Is it pride? He replied: No, pride is disdaining what is true and despising people.
Grade: Sahih

Hadith #4266 - Sunan Abi Dawud - Abdullah bin 'Abdur Rahman b. Abi Sa'sa عبد الله بن عبد الرحمن بن أبي صعصعة; Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abdur Rahman bin 'Abddllah bin 'AR عبد الرحمن بن عبد الله بن عبد الرحمن; Abu Sa'id al-Khudri; Imam Maalik مالك بن أنس بن مالك بن أبي عامر (Sunan Abi Dawud)
Ziyad, one who has white ears.
Grade: Sahih

Hadith #4284 - Sunan Abi Dawud - Abu Sa'id al-Khudri; al-Mandhar bin Malik bin Qata' المنذر بن مالك بن قطعة - أبو نضرة العبدي; Imran bin Da'ud al-'Ami Abu al-'Awwam عمران بن داود العمي أبو العوام القطان; Qatada قتادة; Sahl bin Tmam bin Bzy' سهل بن تمام بن بزيع (Sunan Abi Dawud)
The Prophet (ﷺ) said: The Mahdi will be of my family, of the descendants of Fatimah. Abdullah ibn Ja’far said: I heard AbulMalih praising Ali ibn Nufayl and describing his good qualities.
Grade: Sahih

Hadith #4338 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Abu Sa'id al-Khudri; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; Isma'il bin Raja'a bin Rabi'a al-Zubaidi إسماعيل بن رجاء بن ربيعة الزبيدي; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Qays bin Muslim al-Jadli قيس بن مسلم الجدلي; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Tariq bin Shahab (Sunan Abi Dawud)
You people recite this verse “You who believe, care for yourselves; he who goes astray cannot harm you when you are rightly-guided,” and put it in its improper place. Khalid’s version has: We heard the Prophet (ﷺ) say: When the people see a wrongdoer and do not prevent him, Allah will soon punish them all. Amr ibn Hushaym’s version has: I heard the Messenger of Allah (ﷺ) say: If acts of disobedience are done among any people and do not change them though the are able to do so, Allah
Grade: Sahih

Hadith #4342 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Atyh bin Sa'd bin Jnad'h عطية بن سعد بن جنادة; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Muhammad bin ''Aabadh محمد بن عبادة; Muhammad bin Jahada محمد بن جحادة; Yazid bin Harun يزيد بن هارون (Sunan Abi Dawud)
The Prophet (ﷺ) said: How will you do when that time will come? Or he said: A time will soon come when the people are sifted and only dregs of mankind survive and their covenants and guarantees have been impaired and they have disagreed among themselves and become thus, interwining his fingers. They asked: What do you order us to do, Messenger of Allah? He replied: Accept what you approve, abandon what you disapprove, attend to your own affairs and leave alone the affairs of the generality. Ab
Grade: Sahih

Hadith #4429 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Ahmed bin Manay' أحمد بن منيع; al-Mandhar bin Malik bin Qata' المنذر بن مالك بن قطعة - أبو نضرة العبدي; Fdyl bin Husayn bin Talha فضيل بن حسين بن طلحة; Yazid bin Zari' يزيد بن زريع (Sunan Abi Dawud)
The narrator Hasan b. “All said: The transmitters have differed in the wordings (of this tradition) reported to me. Some said: He (Ma’iz) was tied to a tree, and others said: He was made to stand.
Grade: Hasan

Hadith #4534 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Sa'id al-Khudri; Ahmed bin Salah al-Masri أحمد بن صالح المصري; Amr bin al-Harith bin Ya'qub عمرو بن الحارث; Bukayr bin 'Abdullah bin al-Ashj بكير بن عبد الله بن الأشج (Sunan Abi Dawud)
The Prophet (ﷺ) sent AbuJahm ibn Hudhayfah as a collector of zakat. A man quarrelled with him about his sadaqah (i.e. zakat), and AbuJahm struck him and wounded his head. His people came to the Prophet (ﷺ) and said: Revenge, Messenger of Allah! The Prophet (ﷺ) said: You may have so much and so much. But they did not agree. He again said: You may have so much and so much. But they did not agree. He again said: You may have so much and so much. So they agreed. The Prophet (ﷺ) said: I am go
Grade: Sahih

Hadith #4656 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Abi Dawud)
Al-Aqra’, the mu’adhdhin (announcer) of Umar ibn al-Khattab said: Umar sent me to a bishop and I called him. Umar said to him: Do you find me in the Book? He said: Yes. He asked: How do you find me? He said: I find you (like a) castle. Then he raised a whip to him, saying: What do you mean by castle? He replied: An iron castle and severely trustworthy. He asked: How do you find the one who will come after me? He said: I find him a pious caliph, except that he will prefer his relatives. Umar
Grade: Sahih

Hadith #4665 - Sunan Abi Dawud - Abu Sa'id al-Khudri; al-Mandhar bin Malik bin Qata' المنذر بن مالك بن قطعة - أبو نضرة العبدي; al-Qasim bin al-Fadl bin Ma'dan القاسم بن الفضل بن معدان; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي (Sunan Abi Dawud)
The tradition mentioned above has also been transmitted by Dubai’ah b. Husain al-Tha’labi through a different chain of narrators to the same effect.
Grade: Sahih

Hadith #4666 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Amr bin Yahya bin 'Ammara عمرو بن يحيى بن عمارة; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Wahayb bin Khalid bin 'Ajlan al-Bahli وهيب بن خالد بن عجلان الباهلي; Yahya bin 'Ammara يحيى بن عمارة بن أبي حسن الأنصاري (Sunan Abi Dawud)
I said to ‘All (Allah be pleased with him) : Tell me about this march of yours. Is this an order that the Messenger of Allah (May peace be upon him) had given you, or is this your opinion that you have? He said: The Messenger of Allah (May peace be upon him) did not give me any order; but this is an opinion that I have.
Grade: Sahih

Hadith #4762 - Sunan Abi Dawud - Abdur Rahman bin Abi Na'm عبد الرحمن بن أبي نعم; Abu Sa'id al-Khudri; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sa'id bin Masrooq Ath-Thawri سعيد بن مسروق الثوري; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
various corruptions will arise in my community, so strike with sword the one who tries to cause separation in the matter of Muslims when they are united, whoever he be.
Grade: Sahih

Hadith #4763 - Sunan Abi Dawud - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abu Sa'id al-Khudri; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Anas ibn Malik; Mubashir bin Isma'i مبشر بن إسماعيل - أبو إسماعيل الكلبي; Nsr bin 'Asim al-Antaky نصر بن عاصم الأنطاكي; Qatada قتادة (Sunan Abi Dawud)
‘Ali mentioned about the people of al Nahrawan, saying: Among them there will be a man with a defective hand or with a small hand. if you were not to overjoy. I would inform you of what Allah has promised (the reward for) those who will kill them at the tongue of Muhammad (May peace be upon him). I asked : Have you heard this from him? He replied : Yes, by the lord of the Ka’bah.
Grade: Sahih

Hadith #4813 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Sa'id al-Khudri; Ata ibn Yasar عطاء بن يسار أبو محمد مولى ميمونة; Zayd bin Aslam زيد بن أسلم (Sunan Abi Dawud)
The Prophet (ﷺ) said: If someone is given something, he should give a return for it provided he can afford; if he cannot afford, he should praise him. He who praises him for it, thanks him, and he who conceals it is ungrateful to him. Abu Dawud said: It has been transmitted by Yahya b. Ayyub, from `Umarah b. Ghaziyyah, from Sharahbil on the authority of Jabir. Abu Dawud said: In the chain of this tradition `Umarah b. Ghaziyyah said: A man from my tribe said. The man referred by him is Sharahbi
Grade: Hasan

Hadith #4818 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abdur Rahman bin Abi 'Amra; Abdur Rahman bin Abi al-Mawal عبد الرحمن بن أبي الموال; Abu Sa'id al-Khudri (Sunan Abi Dawud)
A woman came to the Messenger of Allah (ﷺ) and said: Messenger of Allah: I have some need with you. He said to her: Mother of so and so, sit in the corner of any street you wish and I shall sit with you. So she sat and the Messenger of Allah (ﷺ) also sat with her till she fulfilled her need. The narrator Ibn ‘Isa did not mention “till she fulfilled her need.” And Kathir said: from Humaid on the authority of Anas.
Grade: Sahih

Hadith #4830 - Sunan Abi Dawud - Abdullah bin Mubarak عبد الله بن المبارك; Abu Sa'id al-Khudri; al-Walid bin Qays al-Sakuni الوليد بن قيس السكوني; Amr bin 'Awn/'Auf bin Aws; Haywat bin Sharih bin Safwan حيوة بن شريح بن صفوان التجيبي; Salm bin Ghylan al-Tjyby al-Msry سالم بن غيلان التجيبي (Sunan Abi Dawud)
Anas said: We used tell one another that a good companion is like… He then transmitted the rest of the tradition.
Grade: Sahih

Hadith #4844 - Sunan Abi Dawud - Abdur Rahman bin Abi Sa'id al-Khudri عبد الرحمن بن أبي سعيد; Abu Sa'id al-Khudri; Ishaq bin Muhammad al-Ansari إسحاق بن محمد الأنصاري; Rabi' bin 'Abdur Rahman ربيح بن عبد الرحمن بن أبي سعيد الخدري; Salmah bin Shbyb سلمة بن شبيب (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: One should not sit between two men except with their permission.
Grade: Hasan

Hadith #4868 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Abu Sa'id al-Khudri; Hammad bin Usamah حماد بن أسامة - أبو أسامة; Ibrahim bin Musa al-Razi al-Fara' إبراهيم بن موسى الرازي الفراء; Umar ibn al-Khattab (Sunan Abi Dawud)
The Prophet (ﷺ) said: When a man tells something and then departs, it is a trust.
Grade: Sahih

Hadith #5145 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Suhayl bin Abi Salah سهيل بن أبي صالح (Sunan Abi Dawud)
One day when the Messenger of Allah (ﷺ) was sitting, his foster-father came forward. He spread out of a part of his garment and he sit on it. Then his mother came forward to him and he spread out the other side of his garment and she sat on it. Again , his foster-brother came forward. The Messenger of Allah (ﷺ) stood for him and seated him before himself.
Grade: Da'if

Hadith #5178 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Ahmed bin 'Ubda bin Musa أحمد بن عبدة بن موسى; Basr bin Sa'id al-Madni بسر بن سعيد المدني العابد; Sufyan bin 'Uyaynah سفيان بن عيينة; Yazid bin 'Abdullah bin Khusayfa يزيد بن عبد الله بن خصيفة (Sunan Abi Dawud)
Similarly, Musaddad transmitted it to us saying that Abu ‘Awanah related it to us from Mansur. He did not say: “a man of Banu ‘Amir”.
Grade: Sahih

Hadith #5213 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Abu Umama bin Sahl; Hafs bin 'Umar bin al-Harith حفص بن عمر بن الحارث; Sa'd bin Ibrahim سعد بن إبراهيم بن عبد الرحمن; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Abi Dawud)
When the people of the Yemen came, the Messenger of Allah (ﷺ) said: The people of the Yemen have come to you and they are first to shake hands.
Grade: Sahih

Hadith #5254 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
After that, that is, after Abu Lubabah had mentioned him this tradition, Ibn ‘Umar found a snake in his house; he commanded regarding it and it was driven away to al-Baqi’.
Grade: Sahih